Exploration of the Use of Play Money Media in Learning Currency Material in Elementary Schools - Rokhimah, Ratna; Mustoip, Sofyan; Su'aedah, Siti (EduBase : Journal of Basic Education, 2024)
This research aims to explore the use of play money media in learning currency material in elementary schools. The research was conducted with a qualitative approach, using observation methods, in-depth interviews and documentation. The research subjects were teachers and students at an elementary school that had implemented play money as a medium in learning. The research results show that the use of play money can help students understand the concept of the value of money, transaction methods and simple financial management. This media also encourages active student interaction during learning and increases learning motivation. Apart from that, the teacher stated that the play money media made it easier to convey abstract material into a more concrete one. However, this research also found several challenges, such as limited time for preparation and use of media. The implication of this research is the need for support and training for teachers to integrate innovative learning media effectively.